Analysis of Students’s Higher-Order Skills through Project-Based Learning on Acid-Bases Topic - Paristiowati, Maria; Afrizal, Afrizal; Nainggolan, Icha Ananda (IJOSMAS, 2023)
This study aims to analyze higher order thinking skills through a project-based learning model on acid-base material. The project being carried out is to make natural acid-base indicators and to be able to determine the acid-base properties of solutions from the natural acid-base indicators that have been made.This research was conducted from January 2021 to June 2021. This research used a qualitative research method, an interpretive paradigm with 40 students in class XI IPA in Jakarta as subjects. Data collection techniques were carried out by class observation, student and teacher reflective journals, student worksheets and tests of higher order thinking skills.Based on observations, the dominant skill is analyzing skill which is equal to 83.33%, the second skill is evaluating skill which is equal to 79.16%, and the third skill is creating skill amounting to 77.50%. Based on the test results, the dominant skill is analyzing skills by 75.44%, the second skill is evaluating skills by 70.36%, and the third skill is evaluating skills by 69.58%.